Pelatihan Teknis Pengolahan Kue Tradisional dengan Pendekatan Participatory Action Research (PAR) Bagi Santri Pengajian Al- Ikhlas Kota Lhokseumawe - wati, Agustina; muhammad yusuf; cut mislayanti; cut nurfatin shahira (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2025)
Technical training in traditional cake processing using the Participatory Action Research (PAR) method serves as a strategic approach to fostering the independence of students (santri) at Islamic learning centers (balai pengajian). This community service activity aimed to enhance the students’ skills in processing traditional Acehnese cakes, particularly kue gring. The training was conducted at Balai Pengajian Al Ikhlas in Lhokseumawe City. The PAR method was used to encourage active involvement of the students in all stages of the activity, including planning, implementation, observation, and reflection. The results showed that 90% of the participants were able to follow the training process effectively and produce cakes that were suitable for consumption. Moreover, the training also sparked entrepreneurial interest and increased awareness of local culinary heritage among the students. This activity not only improved practical skills but also helped develop independent and productive character. Similar training programs are recommended for other religious study groups, with adjustments based on each region’s local potential.